UTICAJ PREDIKTORSKOG SISTEMA MORFOLOŠKIH KARAKTERISTIKA I MOTORIČKIH SPOSOBNOSTI NA OCJENU IZ PREDMETA TJELESNI I ZDRAVSTVENI ODGOJ - Fahrudin Aščić; Muris Đug; Nenad Katanić; Vahid Dedić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
On a sample of 103 primary school students aged 13 and 14 years, as a prediction variables system, nine variables were applied for the assessment of the morphological characteristics and twelve variables for the evaluation of motor skills. Nine variables were applied as a criterion system from the three sports branches: atheltics, gymnastics and sports games. The goal of this research was to determine a multiple and partial influence of the overall prediction system of morphological characteristics and motor skills on the grade in physical education. Data processing was done by the regression analysis. Statistically significant association of the prediction with the criterion is revealed by the regression analysis of the results of the overall prediction system and the grade form the Physical education. The connection of the given sets is achieved on the statistically significant level, expressed by the multiple correlation coefficient of 67 % and explanatory variables of 44 %. The partial effect of individual variables of morphological characteristics is typologically oriented and focused on the variables of transversal dimension of the skeleton and the variables of longitudinal dimension of the skeleton, while the partial effect of motor ability variables represent the variables that reflect the subspace of the explosive space of lower extremities and the explosive power of arms.